Candle-Light Quantum-Dot Light-Emitting Electrochemical Cells - Shen, Hsiang-Ling; Lu, Chin-Wei; Yang, Zu-Po; Su, Hai-Ching (2024 31st International Workshop on Active-Matrix Flatpanel Displays and Devices (AM-FPD), 2024)
White light sources with low-color temperature have gained popularity in applications promoting healthy lighting, as the impact of blue light on human physiology and psychology is significant. Light-emitting electrochemical cells (LECs) present promising advantages due to their uncomplicated solution fabrication processes, low operational voltage, and compatibility with air-stable cathode metals-qualities beneficial for lighting applications. In this context, LECs mimicking candlelight are developed using blue, green, yellow, and red CdZnSeS/ZnS core-shell quantum dots (QDs). An ionic transition metal complex (iTMC) serves as a carrier injection layer to fme-tune the carrier balance. The resultant white QD LECs demonstrate white electroluminescence (EL) characterized by a low correlated color temperature (CCT) below 1800 K and a high color rendering index (CRI) exceeding 90 under lower currents. These white QD LECs boast EL spectra with CCTs among the lowest reported values for white LECs, showcasing their exceptional capability for color tuning through mixed QD emissive layers.